The Relationship Between Gender and Students' Knowledge and Attitudes Towards Healthy Snack Selection in Semarang City Public Elementary Schools - Mulyawati, Isti; Zulfa, Nely; Sudrajat, Agus (Universitas Karya Husada Semarang, 2026)
Background: The habit of eating snacks at school is part of the diet of elementary school students who need attention related to their nutritional quality. Knowledge and attitude are often considered determining factors in choosing healthy snacks. Objective: This study aims to analyze the relationship between gender and students' knowledge and attitudes towards choosing healthy snacks at Semarang City State Elementary School. Methods: Quantitative study with cross- sectional design. The sample consisted of 74 students taken from 21 State Elementary Schools in Semarang City using quota sampling techniques. Data was collected through a structured questionnaire and analyzed using Chi-Square statistical tests. Results: The univariate analysis showed that the majority of respondents were female (59.5%), had good knowledge (89.2%), and had good attitudes (41.9%). The results of the bivariate analysis showed no relationship between gender and knowledge of healthy snack selection (p value= 1.00) and no relationship between gender and attitudes towards healthy snack selection (p value = 0.196). Conclusion: Gender is not a distinguishing factor in students' knowledge and attitudes towards healthy snacks. This suggests that school health interventions should focus more on strengthening the physical environment and the availability of healthy snacks in schools, regardless of gender.